Determination of Differentiating Markers in Coicis Semen From Multi-Sources Based on Structural Similarity Classification Coupled With UPCC-Xevo G2-XS QTOF - Zhu, Ruyi; Xu, Xiaofen; Shan, Qiyuan; Wang, Kuilong; Cao, Gang; Wu, Xin (Frontiers in Pharmacology, 2020)
Coicis semen, a medicinal food, is derived from the dried and mature seeds of Coix lacryma-jobi L. var. ma-yuen (Rom.Caill.) Stapf, a member of the Gramineae family. Lipids are its main constituents. Previous literature reported that coicis semen contains twenty triglycerides and twelve diglycerides. However, we identified thirty-five triglycerides, sixteen diglycerides, four monoglycerides, and two sterols under the preoptimized conditions of UPCC-Xevo G2-XS QTOF combined with a personalized TCM database. Furthermore, we successfully determined glycerol trioleate content to evaluate quality differences. Finally, we identified the fatty acid compositions of seven out of nine differential markers via Progenesis QI using principal component analysis, orthogonal projection to latent structures–discriminant analysis, and the LipidMaps database. In addition, we applied a software-based classification, a method that was previously developed by our team, to verify and predict structurally similar compounds. Our findings confirmed that UPCC-Xevo G2-XS QTOF combined with software-based group classification could be used as an efficient method for exploring the potential lipid markers of seed medicine.